Effect of Normalizing on the Tensile Strength, Shrinkage and Surface Roughness of PLA Plastic. (2020) - Singh, S.; Rajeshkannan, A.; Feroz, S.; Jeevanantham, A.K.
Abstract: The two major methods of altering the properties of a material include alloying and heat treatment processes. Out of the several heat treatment processes, normalizing is one in which air is used as a cooling media after the material has reached its recrystallization temperature. This project explores the effects of normalizing on the tensile strength of a chosen material, in this case as PLA (Polylactic Acid) plastic. The research also extended to investigate the effects of normalizing on surface roughness and shrinkage. The investigation follows a strategic and systematic approach whereby the methodology used to conduct the experiments gave a quantitative output. In general it was found that the heat treatment makes significant impact on the chosen property.